P2Y2R Signaling Is Involved in the Onset of Glomerulonephritis - Rennert, Laura; Zschiedrich, Stefan; Sandner, Lukas; Hartleben, Björn; Cicko, Sanja; Ayata, Cemil Korcan; Meyer, Charlotte; Zech, Andreas; Zeiser, Robert; Huber, Tobias B.; Idzko, Marco; Grahammer, Florian (Frontiers in Immunology, 2018)
Abstract Endogenously released ATP is a key regulator of physiological and inflammatory responses in the kidney. Genetic or pharmacological inhibition of purinergic receptors has been linked to attenuation of inflammatory disorders and hence constitutes promising new avenues for halting and reverting inflammatory renal diseases. However the involvement of purinergic receptors in glomerulonephritis has only been incompletely mapped. Here we demonstrate that induction of glomerulonephritis (GN) in an experimental antibody-mediated GN model results in a significant increase of urinary ATP-levels and an up-regulation of P2Y2R expression in resident kidney cells as well as infiltrating leukocytes pointing towards a possible role of the ATP/P2Y2R-axis in glomerular disease initiation. In agreement, decreasing extracellular ATP-levels or blocking of P2R during induction of antibody-mediated GN leads to a reduction in all cardinal features of GN such as proteinuria, glomerulosclerosis and renal failure. The specific involvement of P2Y2R could be further substantiated by demonstrating the protective effect of the lack of P2Y2R in antibody-mediated GN. To systematically differentiate between the function of P2Y2R on resident renal cells versus infiltrating leukocytes we performed bone marrow-chimera experiments revealing that P2Y2R on hematopoietic cells is the main driver of the ATP/P2Y2R mediated disease progression in antibody-mediated GN. Thus, these data unravel an important pro-inflammatory role for P2Y2R in the pathogenesis of glomerulonephritis. Keywords: Glomerulonephritis, leukocytes, purinergic receptors, P2Y2, ATP, animal model,